Evaluation of fire protection system at UNIMAS mechanical laboratory - Mastura, Mohamad (Universiti Malaysia Sarawak, UNIMAS, 2006)
Safety is the most important aspect in life nowadays. Fire safety is one of the building premier considerations for life safety of occupants of the building. Fire safety is a performance characteristic of a buildings. This paper is about the evaluation of fire protection system of Mechanical Laboratory (CNC Laboratory). From the evaluation, it was fou nd that the Mechanical Laboratory does not conform to BOMBA requirement, whereby all the necessary fire protection equipment and system is not in placed. This project has proposed the required fire protection system in accordance to BOMBA requirement ( Unif orm Building By - Law, 1984 and Sarawak Building Ordinance, 1994 ) . Where the installation of fire extinguisher (CO 2 ), fire alarm with break glass, panel, fire hydrant, heat detector, smoke detector, emergency light, signage, fire door and fire resistant wind ow is required and the location of respective equipment is presented in this report.